Wpływ pracy w szkolnym projekcie na zachowanie studentów - Abu-Ahmed, Laila (Studia Edukacyjne, 2020)
This article describes a school intervention program that was initiated and developed by a small team in one of the schools in the city of Nazareth, Israel. The proposed program is intended to promote academic perseverance and thereby reduce dropout rates, providing youth at risk with a variety of personal and interpersonal skills that are important both for studies and for labor world. The findings showed that combining learning with work in the candle factory promoted attendance and reduced violent behavior in school.